Soil impacts on UK infrastructure: current and future climate - Pritchard, Oliver G.; Hallett, Stephen H.; Farewell, Timothy (Institution of Civil Engineers (ICE), 2014)
This paper undertakes a critical review of the literature concerning mechanisms and impacts of soil-related geohazards to UK infrastructure. The country is predicted to have drier, hotter summers and wetter, warmer winters that in turn will increase the magnitude and frequency of many soil-related geohazards – predominantly due to changes in soil moisture. Probabilistic assessment will be required given the inherent uncertainty in assessing chronic soil hazards. The aim of this paper is to recommend a national framework methodology to aid the management of future risks posed by soil geohazards to UK infrastructure. The framework will help to prioritise ground investigations in high-risk areas, help to design suitable mitigation measures and encapsulate expert knowledge to interpret risk.